Analisis Pemasaran Wisata Kuliner Terhadap Peningkatan Pendapatan Masyarakat di Kabupaten Kerinci - Gampo Haryono; Edia Satria; Ayu Esteka Sari (Universitas Batanghari, 2019)
The importance of a tourist destination in promoting cultural heritage and indeed its contribution to the tourism industry as a whole. Diversity in culture must be seen as a strength in the marketing of food tourism. The impact of culinary tourism is huge and can improve the overall economy of any country. Tourists are more inclined to continue to demand more traditional food because this allows access to cultural and historical heritage of various cultures to make it more authentic. Culinary arts is one of the attractions for tourists who are traveling with the aim of enjoying various types of food typical of places that are headed. Culinary tourism is part of agribusiness that focuses specifically on searching for, and enjoying, preparing food and drinks. Several goals have taken the concept of sustainability to a new level and have begun to offer food and beverage oriented. The research method used in this research is descriptive method with data processing in this study carried out qualitatively and quantitatively, with Analytical Hierarchy Process (AHP) analysis. Analytical Hierarchy Process (AHP) is used as a tool to determine which strategies should be prioritized by the Kerinci Regency to support the marketing activities of Culinary Tourism.